Analysis of molecular mechanisms of 5-fluorouracil-induced steatosis and inflammation in vitro and in mice - Sommer, Judith; Mahli, Abdo; Freese, Kim; Schiergens, Tobias S.; Kuecuekoktay, Fulya Suzan; Teufel, Andreas; Thasler, Wolfgang E.; Mueller, Martina; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Oncotarget, 2017)
Chemotherapy-associated steatohepatitis is attracting increasing attention because it heralds an increased risk of morbidity and mortality in patients undergoing surgery because of liver metastases. The aim of this study was to develop in vitro and in vivo models to analyze the pathogenesis of 5-fluorouracil (5-FU)-induced steatohepatitis.Therefore, primary human hepatocytes and HepG2 hepatoma cells were incubated with 5-FU at non-toxic concentrations up to 24 h. Furthermore, hepatic tissue of C57BL/6N mice was analyzed 24 h after application of a single 5-FU dose (200 mg/kg body weight). In vitro, incubation with 5-FU induced a significant increase of hepatocellular triglyceride levels. This was paralleled by an impairment of mitochondrial function and a dose- and time-dependently increased expression of fatty acid acyl-CoA oxidase 1 (ACOX1), which catalyzes the initial step for peroxisomal ?-oxidation. The latter is known to generate reactive oxygen species, and consequently, expression of the antioxidant enzyme heme oxygenase 1 (HMOX1) was significantly upregulated in 5-FU-treated cells, indicative for oxidative stress. Furthermore, 5-FU significantly induced c-Jun N-terminal kinase (JNK) activation and the expression of pro-inflammatory genes IL-8 and ICAM-1. Also in vivo, 5-FU significantly induced hepatic ACOX1 and HMOX1 expression as well as JNK-activation, pro-inflammatory gene expression and immune cell infiltration. In summary, we identified molecular mechanisms by which 5-FU induces hepatocellular lipid accumulation and inflammation. Our newly developed models can be used to gain further insight into the pathogenesis of 5-FU-induced steatohepatitis and to develop therapeutic strategies to inhibit its development and progression.
EVALuna2:4753

Bone Morphogenetic Protein 13 Has Protumorigenic Effects on Hepatocellular Carcinoma Cells In Vitro. - Kersten, Vanessa; Seitz, Tatjana; Sommer, Judith; Thasler, Wolfgang E.; Boßerhoff, Anja Katrin; Hellerbrand, Claus (International Journal of Molecular Sciences, 2023)
Activated hepatic stellate cells (HSCs) play a key role in hepatic fibrosis and, thus, build the "soil" for hepatocarcinogenesis. Furthermore, HSCs are known to promote the progression of hepatocellular carcinoma (HCC), but the molecular mechanisms are only incompletely understood. Recently, we newly described the expression of bone morphogenetic protein 13 (BMP13) by HSCs in fibrotic liver tissue. In addition, BMP13 has mostly been studied in the context of cartilage and bone repair, but not in liver disease or cancer. Thus, we aimed to analyze the expression and function of BMP13 in HCC. Expression analyses revealed high BMP13-expression in activated human HSCs, but not in human HCC-cell-lines. Furthermore, analysis of human HCC tissues showed a significant correlation between BMP13 and α-smooth muscle actin (α-SMA), and immunofluorescence staining confirmed the co-localization of BMP13 and α-SMA, indicating activated HSCs as the cellular source of BMP13 in HCC. Stimulation of HCC cells with recombinant BMP13 increased the expression of the inhibitors of differentiation 1 (ID1) and 2 (ID2), which are known targets of BMP-signaling and cell-cycle promotors. In line with this, BMP13-stimulation caused an induced SMAD 1/5/9 and extracellular signal-regulated kinase (ERK) phosphorylation, as well as reduced expression of cyclin-dependent kinase inhibitors 1A (CDKN1A) and 2A (CDKN2A). Furthermore, stimulation with recombinant BMP13 led to increased proliferation and colony size formation of HCC cells in clonogenicity assays. The protumorigenic effects of BMP13 on HCC cells were almost completely abrogated by the small molecule dorsomorphin 1 (DMH1), which selectively blocks the intracellular kinase domain of ALK2 and ALK3, indicating that BMP13 acts via these BMP type I receptors on HCC cells. In summary, this study newly identifies stroma-derived BMP13 as a potential new tumor promotor in HCC and indicates this secreted growth-factor as a possible novel therapeutic target in HCC.
EVALuna2:538506

Bone morphogenetic protein 13 in hepatic stellate cells and hepatic fibrosis - Peschl, Vanessa; Seitz, Tatjana; Sommer, Judith; Thasler, Wolfgang; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Journal of Cellular Biochemistry, 2022)
Hepatic fibrosis can be considered as a deregulated wound healing process in response to chronic liver injury. Bone morphogenetic protein 13 (BMP13) has been described to promote bone and tendon repair. In this study, we aimed to analyze the expression and function of BMP13 in hepatic fibrosis. We found increased BMP13 expression during the activation of hepatic stellate cells (HSCs), which is known as the key event of hepatic fibrosis. Fitting to this, BMP13 was elevated in murine models of hepatic fibrosis, and immunofluorescence staining showed colocalization of BMP13 and α-smooth muscle actin (α-SMA), a marker for activated HSC, in cirrhotic human liver tissue. BMP13 depletion in activated human HSC reduced the phosphorylation of smad1/5/9 and the expression of the transcription factor inhibitor of differentiation 1 (ID1), a known BMP target gene and profibrogenic factor. Furthermore, BMP13-depletion led to reduced proliferation and downregulation of collagen I α1 (COL1A1) and α-SMA, and, interestingly, also reduced phosphorylation of extracellular signal-regulated kinases (ERK). Conversely, stimulation with recombinant BMP13 induced the phosphorylation of smad1/5/9 and ERK, as well as the proliferation and the expression of ID1, COL1A1, and α-SMA in HSCs. These stimulatory effects were inhibited by dorsomorphin 1, a small-molecule inhibitor of the BMP-type I receptors activin receptor-like kinase-2 and -3, which are both expressed by HSC. In summary, these data indicate increased BMP13 expression in hepatic fibrosis as a profibrogenic factor. Thus, this soluble growth factor might have the potential as a new fibrosis marker and antifibrogenic therapeutic target in patients with chronic liver disease.
CRIS-Team Scopus Importer:2022-04-29
Keywords: BMP13; hepatic stellate cells; liver fibrosis

Expression of Bone Morphogenetic Protein 14 in Liver Disease and Cancer - Sommer, Judith; Thasler, Wolfgang E.; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Livers, 2023)
The activation of hepatic stellate cells (HSCs) is the key event of hepatic fibrosis. Furthermore, activated HSCs also play an important role in the progression of hepatocellular cancer (HCC). Bone morphogenetic protein 14 (BMP14) is a member of the TGF-β/BMP superfamily. So far, most studies have analyzed BMP14 in the context of bone and cartilage formation and homeostasis. The aim of this study was to assess the expression and function of BMP14 in liver fibrosis and HCC. The BMP14 expression increased during the in vitro activation of primary human HSCs and also in mouse models of liver fibrosis. In human HCC, as well as non-tumorous liver tissues, there was a significant correlation between the expression of BMP14 and alpha-smooth-muscle actin (α-SMA), an established marker for HSC activation. RNAi-mediated BMP14 suppression in activated HSCs resulted in the reduced expression of the transcription factors inhibitor of differentiation 1 (ID1) and ID2, known targets of BMP signaling. Interestingly, α-SMA and collagen expression was also reduced in BMP14-depleted cells, while treatment with recombinant BMP14 induced ID1, ID2, α-SMA and collagen expression. In human HCC cell lines, treatment with recombinant BMP14 induced proliferation, migratory activity and colony formation. In summary, our data indicate activated HSCs as a major cellular source of enhanced BMP14 expression in fibrotic liver disease and HCC, and show that BMP14 exhibits pro-fibrogenic as well as pro-tumorigenic effects. Future analyses will reveal the potential of this soluble growth factor as a therapeutic target or prognostic marker for the progression of fibrosis and HCC in patients with chronic liver disease.
CRIS-Team Scopus Importer:2023-11-17
Keywords: BMP14; hepatic stellate cells; hepatocellular cancer; liver fibrosis

Four-And-A-Half LIM-Domain Protein 2 (FHL2) Deficiency Aggravates Cholestatic Liver Injury - Sommer, Judith; Dorn, Christoph; Gaebele, Erwin; Bataille, Frauke; Freese, Kim; Seitz, Tatjana; Thasler, Wolfgang E.; Buettner, Reinhard; Weiskirchen, Ralf; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cells, 2020)
Cholestasis occurs in different clinical circumstances and leads to severe hepatic disorders. The four-and-a-half LIM-domain protein 2 (FHL2) is a scaffolding protein that modulates multiple signal transduction pathways in a tissue- and cell context-specific manner. In this study, we aimed to gain insight into the function of FHL2 in cholestatic liver injury. FHL2 expression was significantly increased in the bile duct ligation (BDL) model in mice. In Fhl2-deficient (Fhl2-ko) mice, BDL caused a more severe portal and parenchymal inflammation, extended portal fibrosis, higher serum transaminase levels, and higher pro-inflammatory and pro-fibrogenic gene expression compared to wild type (wt) mice. FHL2 depletion in HepG2 cells with siRNA resulted in a higher expression of the bile acid transporter Na+-taurocholate cotransporting polypeptide (NTCP) gene. Furthermore, FHL2-depleted HepG2 cells showed higher expression of markers for oxidative stress, lower B-cell lymphoma 2 (Bcl2) expression, and higher Bcl2-associated X protein (BAX) expression after stimulation with deoxycholic acid (DCA). In hepatic stellate cells (HSCs), FHL2 depletion caused an increased expression of TGF-β and several pro-fibrogenic matrix metalloproteinases. In summary, our study shows that deficiency in FHL2 aggravates cholestatic liver injury and suggests FHL2-mediated effects on bile acid metabolisms and HSCs as potential mechanisms for pronounced hepatocellular injury and fibrosis.
EVALuna2:212289

Four-and-a-Half LIM-Domain Protein 2 (FHL2) Induces Neuropeptide Y (NPY) in Macrophages in Visceral Adipose Tissue and Promotes Diet-Induced Obesity - Sommer, Judith; Ehnis, Hanna; Seitz, Tatjana; Schneider, Julia; Wild, Andreas; Moceri, Sandra; Buechler, Christa; Bozec, Aline; Weber, Georg; Merkel, Susanne; Beckervordersandforth, Ruth; Steinkasserer, Alexander; et al. (International Journal of Molecular Sciences, 2023)
Obesity is characterized by the expansion of the adipose tissue, usually accompanied by inflammation, with a prominent role of macrophages infiltrating the visceral adipose tissue (VAT). This chronic inflammation is a major driver of obesity-associated comorbidities. Four-and-a-half LIM-domain protein 2 (FHL2) is a multifunctional adaptor protein that is involved in the regulation of various biological functions and the maintenance of the homeostasis of different tissues. In this study, we aimed to gain new insights into the expression and functional role of FHL2 in VAT in diet-induced obesity. We found enhanced FHL2 expression in the VAT of mice with Western-type diet (WTD)-induced obesity and obese humans and identified macrophages as the cellular source of enhanced FHL2 expression in VAT. In mice with FHL2 deficiency (FHL2KO), WTD feeding resulted in reduced body weight gain paralleled by enhanced energy expenditure and uncoupling protein 1 (UCP1) expression, indicative of activated thermogenesis. In human VAT, FHL2 was inversely correlated with UCP1 expression. Furthermore, macrophage infiltration and the expression of the chemokine MCP-1, a known promotor of macrophage accumulation, was significantly reduced in WTD-fed FHL2KO mice compared with wild-type (wt) littermates. While FHL2 depletion did not affect the differentiation or lipid metabolism of adipocytes in vitro, FHL2 depletion in macrophages resulted in reduced expressions of MCP-1 and the neuropeptide Y (NPY). Furthermore, WTD-fed FHL2KO mice showed reduced NPY expression in VAT compared with wt littermates, and NPY expression was enhanced in VAT resident macrophages of obese individuals. Stimulation with recombinant NPY induced not only UCP1 expression and lipid accumulation but also MCP-1 expression in adipocytes. Collectively, these findings indicate that FHL2 is a positive regulator of NPY and MCP-1 expression in macrophages and herewith closely linked to the mechanism of obesity-associated lipid accumulation and inflammation in VAT. Thus, FHL2 appears as a potential novel target to interfere with the macrophage–adipocyte crosstalk in VAT for treating obesity and related metabolic disorders.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adipocytes; FHL2; macrophages; MCP-1; NPY; obesity; thermogenesis

Four-and-a-half LIM-domain protein affects diet induced (hepatic) steatosis and lipid droplet formation - Sommer, Judith; Hellerbrand, Claus (JOURNAL OF HEPATOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-26

Role of Fibroblast Growth Factors in the Crosstalk of Hepatic Stellate Cells and Uveal Melanoma Cells in the Liver Metastatic Niche - Seitz, Tatjana; John, Nora; Sommer, Judith; Dietrich, Peter; Thasler, Wolfgang E.; Hartmann, Arndt; Evert, Katja; Lang, Sven A.; Boßerhoff, Anja Katrin; Hellerbrand, Claus (International Journal of Molecular Sciences, 2022)
Hepatic metastasis is the critical factor determining tumor-associated mortality in different types of cancer. This is particularly true for uveal melanoma (UM), which almost exclusively metastasizes to the liver. Hepatic stellate cells (HSCs) are the precursors of tumor-associated fibroblasts and support the growth of metastases. However, the underlying mechanisms are widely unknown. Fibroblast growth factor (FGF) signaling is dysregulated in many types of cancer. The aim of this study was to analyze the pro-tumorigenic effects of HSCs on UM cells and the role of FGFs in this crosstalk. Conditioned medium (CM) from activated human HSCs significantly induced proliferation together with enhanced ERK and JNK activation in UM cells. An in silico database analysis revealed that there are almost no mutations of FGF receptors (FGFR) in UM. However, a high FGFR expression was found to be associated with poor survival for UM patients. In vitro, the pro-tumorigenic effects of HSC-CM on UM cells were abrogated by a pharmacological inhibitor (BGJ398) of FGFR1/2/3. The expression analysis revealed that the majority of paracrine FGFs are expressed by HSCs, but not by UM cells, including FGF9. Furthermore, the immunofluorescence analysis indicated HSCs as a cellular source of FGF9 in hepatic metastases of UM patients. Treatment with recombinant FGF9 significantly enhanced the proliferation of UM cells, and this effect was efficiently blocked by the FGFR1/2/3 inhibitor BGJ398. Our study indicates that FGF9 released by HSCs promotes the tumorigenicity of UM cells, and thus suggests FGF9 as a promising therapeutic target in hepatic metastasis.
CRIS-Team Scopus Importer:2022-10-28
Keywords: fibroblast growth factor 9; fibroblast growth factors; hepatic metastasis; hepatic stellate cells; uveal melanoma

STEATOSIS: A LUBRICANT FOR THE DEVELOPMENT AND PROGRESSION OF ALCOHOLIC LIVER DISEASE - Mahli, Abdo; Sommer, Judith; Koch, A.; Hellerbrand, Claus (ALCOHOLISM-CLINICAL AND EXPERIMENTAL RESEARCH, 2021)
CRIS-Team WoS Importer:2021-07-02